Kepemimpinan Kepala Sekolah dalam Pemulihan dan Transformasi Pembelajaran di Lembaga Pendidikan Formal: Studi Kasus SD dan SMP Negeri di Kota Palembang - Elya Widiyanti; Aliya Shabirah; Mardalena Mardalena; Nursilawati Nursilawati; Dessy Wardiah; Eni Heldayani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
This study aims to analyze the effect of transformational leadership of school principals on students’ digital literacy through the school digital ecosystem and teacher innovation as mediating variables. The research employed a quantitative approach with an explanatory research design and was analyzed using Structural Equation Modeling (SEM). The sample consisted of teachers at primary and secondary education levels who have implemented technology-based learning. The results show that transformational leadership has a positive and significant effect on the school digital ecosystem. Furthermore, the digital ecosystem significantly influences teacher innovation, and teacher innovation has a significant effect on students’ digital literacy. The findings also reveal that transformational leadership indirectly affects students’ digital literacy through the school digital ecosystem and teacher innovation. These results indicate that improving students’ digital literacy is not solely determined by technological factors but also by school leadership and pedagogical innovation. Therefore, a synergy between transformational leadership, strengthening of the digital ecosystem, and enhancement of teacher innovation is essential to create adaptive learning in the digital era.